Severe Hyperphosphatemia in a Patient with Mild Acute Kidney Injury - Phuong Chi Pham; Raghu Konanur Ventakaram; Jimmy Pham; Harpreet Sidhu; Nada Bader; Phuong Mai Pham; Phuong Thu Pham (Case Reports in Medicine)
Hyperphosphatemia may arise from various conditions including exogenous ingestion, extracellular shifts due to cell death or alterations in acid-base status, increased bone resorption, hormonal dysregulations leading to reduced renal excretion, reduced kidney function, or faulty measurement techniques. We herein present a case of a young pregnant woman who presented with mild acute kidney injury (AKI), invasive mucormycosis receiving liposomal amphotericin, and hyperphosphatemia out of proportion to the degree of kidney injury. While the patient was given routine phosphate-binding agent by her primary care team for presumed AKI-associated hyperphosphatemia, a full investigation by the renal consulting team for contributing factors other than kidney injury revealed that she actually had pseudohyperphosphatemia associated with the use of liposomal amphotericin. Erroneous treatment of pseudohyperphosphatemia may have been detrimental to this pregnant patient. A literature review for conditions associated with pseudohyperphosphatemia other than the use of liposomal amphotericin will be discussed.